Integrated Management for Patients with Diabetes Mellitus: A Literature Review - Haris, Fahni; Fadhilah, Ais Izza; Relawati, Ambar; Irawati, Kellyana; Rahman, Ferry Fadzlul; Rusyani, Yeni; Pentrakan, Amarawan (Universitas Muhammadiyah Yogyakarta, 2023)
Background: Many factors contribute to DM, such as age, heredity, high-calorie meals, an unhealthy lifestyle, obesity, and stress. Inadequate glycemic control contributes to elevated blood glucose levels and potential complications. However, many people of DM had unmet proper DM management regularly due to many factors.Objective: This study reviewed published articles about integrated management for people with DM through three databases.Methods: We identified 1902 articles, and 13 articles were selected for full-text analysis.Results: We found that in integrated DM management for patients with DM, they highly recommend to monitoring their blood glucose, doing exercise, dietary plan, coping strategy, and continuous health education were the most effective DM management strategies to lowering HbA1c levels.Conclusion: Nurses as healthcare providers should engage with people with DM to ensure they have good knowledge and understanding of how to maintain their disease.